HUBUNGAN TINGKAT PENGETAHUAN ASMA DENGAN TINGKAT KONTROL ASMA DI POLIKLINIK PARU RSUD ARIFIN ACHMAD PEKANBARU - Syahira "; Indra Yovi; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAsthma is a chronic inflammatory process in the respiratory tract. In the process of respiratory tract will be hiperesponsif. The level of asthma knowledge is essential to achieve the level of asthma control. Patients and families can understand asthma with either consciously would avoid trigger factors attacks. This study aims to determine the relationship of the level asthma knowledge to the level of asthma control in the pulmonary clinic Arifin Achmad Pekanbaru. This study uses an analytical method with cross sectional approach. The sampling technique used in the formula n= and the obtained value n = 97 people. The study was held on February-May 2015 at the pulmonary polyclinic of Arifin Achmad general hospital Pekanbaru. The results of this study with the most level of knowledge asthma is higher 72 people (74%), the level of uncontrolled asthma control 77 people (79.4%), based on age 18-45 years are 51 people (52.6% ), most are female gender 62 people (64%). Most jobs are housewives 47 people (48.5%). Relations with the level asthma knowledge level of and asthma control by chi square’s test found no significant relationship between the level asthma knowledge to the level of asthma control with p = 0.843 (p <0.5).Keywords: Level of asthma general knowledge, asthma control level